Waveform design for improved range and Doppler resolution in radar - Farid, Ghani, Prof. Dr.; Mohd Alif Hasmani, Abd Ghani; Siti Julia, Rosli; R. Badlishah, Ahmad, Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/